Case Report: Everolimus reduced bone turnover markers but showed no clinical benefit in a patient with severe progressive osseous heteroplasia - M. Cebey-López; M. Cebey-López; M. J. Currás-Tuala; M. J. Currás-Tuala; J. Gómez-Rial; J. Gómez-Rial; J. Gómez-Rial; I. Rivero-Calle; I. Rivero-Calle; J. Pardo-Seco; J. Pardo-Seco; R. Mendez-Gallart; et al. (Frontiers Media S.A., 2022)
BackgroundProgressive osseous heteroplasia (POH) is an ultrarare genetic disorder characterized by an inactivating mutation in the GNAS gene that causes heterotopic ossification. Inhibition of the mammalian target of the rapamycin (mTOR) signalling pathway has been proposed as a therapy for progressive bone fibrodysplasia and non-genetic forms of bone heteroplasia. Herein, we describe the impact of using Everolimus as a rescue therapy for an identical twin girl exhibiting an aggressive clinical phenotype of POH.MethodsClinical evaluation of the progression of the disease during Everolimus treatment was performed periodically. Cytokine markers involved in bone metabolism and protein markers related to bone activity were analyzed to explore bone turnover activity.ResultsThe patient received Everolimus therapy for 36 weeks. During treatment, no clinical improvement of the disease was perceived. Analysis of biochemical parameters, namely, β-CTX (r2 = −0.576, P-value = 0.016) and PNIP (r2 = −0.598, P-value = 0.011), indicated that bone turnover activity was significantly reduced. Additionally, bone metabolism-related biomarkers showed only a significant positive correlation with PTH levels.ConclusionsEverolimus treatment did not modify the clinical progression of the disease in an aggressive form of POH, although an impact on the protein markers studied was observed.